Regularity criteria for the 3D density-dependent incompressible Maxwell–Navier–Stokes system. (1st June 2017) - Fan, Jishan; Zhou, Yong
Abstract: This paper proves some regularity criteria for the 3D (density-dependent) incompressible Maxwell–Navier–Stokes system, which improves a recent result of Kang and Lee (2013).